If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3p + 2p = 4 Combine like terms: -3p + 2p = -1p -1p = 4 Solving -1p = 4 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '-1'. p = -4 Simplifying p = -4
| 3x+17=32 | | k+4+3=1 | | 1.5c+c=20 | | x+1+6=6 | | k+7+8=19 | | 3x+2-6x=-7 | | -3m-8m=-11 | | -5x+x=4 | | -5n+3n=-10 | | 65-6X=12X+19 | | 9u^2-36v^2= | | 4+2a+6a=12 | | 4*x=60 | | 2n+5n=-21 | | 75x^3-12x=0 | | 49y^2-28y+4= | | v+1+4=10 | | m^3+6m^2-4m=0 | | a^2+8a-15=0 | | 116-4x=23x+17 | | ln(13)+ln(x)=0 | | 7b+1-b=1 | | x+7=-2(4x+10) | | 7-9x=46-30x | | 184-4x=41x+19 | | 6+x=-13 | | -42+y+2=44 | | y^2+6y-7=17 | | -x^2+6x-5=y | | -2n-n=-12 | | -7+6=x | | 9-10x=89-24x |